Demographic Projections for India: Past, Present and Future - Subba Rao, R; Jagannadhapuri, Y; M. Ganes, K; V. Ramanamurthy, D (International Journal of Engineering and Technology, 2018)
The growth or development of a country mainly depends on the present and future population scenario. Population projections help in the growth of the nation in various directions. Predicting the human fertility and mortality is very difficult, particularly when we are concentrating farther time. Various National, International and some individual demographers made projections for the entire nation and some parts of the country. The estimates of the population projections changes as and when new information added to the existing values. The perspective population growth and its impact were discussed by Visaria and Visaria, 1996 and noticed that population projections vary based on the parameters considered in their models.Â In our present work, by considering the 2001 Indiaâ€™s Census data, Registrar General (1996)[14], a new population projection of the country are estimated by allowing the age arrangement of the population. The mortality estimates of the whole country made by considering the impact of HIV / AIDS. Cohort component method was used for the projections from 2001 to 2051. Using the Sample Registration System (SRS) figures of 2001 census, state level figures are generated. Only two variants namely, average and high are used for making the population projections.Â Â